Facial scrub cream contained ginger-enzyme - Burakorn, Jiraporn; Subtaeng, Subongkoch; Tongmanee, Jitrekha; Preeprame, Srisomporn (Bulletin of Applied Sciences, 2022)
This study was performed to develop facial scrub cream containing ginger enzyme. It was found that activity and specific activity of the crude ginger protease were 15 Units/ml/min and and 377 Units/mg protein, respectively. First, a crude preparation of ginger protease was lyophilized using a freeze dryer. Its stability was improved by mixing casein and borox and the protease powder. The specific activity value of the stabilized ginger protease was 1,025 Units/mg protein. The stabilized ginger protease was mixed with scrub cream. The mixture contain 20% (w/w) of the enzyme, equivalent to 9.9 Unit/ml/min. Then, the ginger enzyme scrub cream was tested on animals for primary irritant properties. No irritation was observed, as indicated by the primary irritation index of 0.6. In the efficiency study, the ginger enzyme scrub cream and control scrub cream were used by 20 healthy female for 14 days. There were no significant difference between the ginger enzyme scrub cream and the control scrub cream. Besides, dark spots on faces of certain volunteers who used the ginger enzyme scrub cream were dramatically decreased. The volunteers satisfaction on the quality, brightness, moisturizer, wrinkle and total satisfaction of the ginger enzyme scrub cream were evaluated by the questionnaires. The results showed that the volunteers were more satisfied with the ginger enzyme scrub cream than the control scrub cream, as shown by total satisfaction score of 90 and 64%, respectively.